Performance Evaluation of Different Types of Additive Manufacturing Electrodes Fabricated by Fused Deposition Modelling (FDM) on Machining Mild Steel - Ng, Nicolas; Haq bin Abdul Haq, Reazul (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The manufacturing of an electrode accounts for more than 50% of the total cost and time of a sinker Electrical Discharge Machining (EDM) operation. This study aims to study indirect Rapid Tooling (RT) electrode production to reduce fabrication costs and time. Polyethylene Terephthalate Glycol (PETG) and electrically conductive Polylactic Acid (PLA) were chosen as the electrode core material. In addition, the feasibility of metallization on the Fused Deposition Modelling (FDM) electrodes was investigated. Furthermore, the machining performance and characterization of the EDM electrodes were evaluated. For primary metallization, the dipping and hanging of the cylindrical sample with copper conductive paint produced a better coating than the aluminium paste method. Even though both methods have their drawbacks, nearly the entire cylindrical sample was coated when it was dipped into the paint. However, unfilled sections and uneven coating were formed when the aluminium paste method was tested. Therefore, future studies should attempt new methods to improve the primary metallization's initial coating quality and fabrication time.